Large cell neuroendocrine lung carcinoma induces peripheral T-cell repertoire alterations with predictive and prognostic significance. (May 2018) - Christopoulos, Petros; Schneider, Marc A.; Bozorgmehr, Farastuk; Kuon, Jonas; Engel-Riedel, Walburga; Kollmeier, Jens; Baum, Volker; Muley, Thomas; Schnabel, Philipp A.; Bischoff, Helge; Grohé, Christian; Serke, Monika; et al.
Highlights: Blood T-cell repertoire alterations and lymphopenia are common in LCNEC patients. Pretreatment spectratype alterations correlate positively with blood lymphocyte counts. Both parameters confer better response to treatment and longer survival in LCNEC. Partial restoration of T-cell repertoire with therapy also predicts longer survival. Abstract: Objectives: This study was performed to evaluate for a potentially important role of T cells in the pathophysiology and treatment sensitivity of large cell neuroendocrine lung carcinoma (LCNEC), an orphan disease with poor prognosis and scarce data to guide novel therapeutic strategies. Materials and methods: We performed T-cell receptor (TCR) β-chain spectratyping on blood samples of patients treated within the CRAD001KDE37 trial (n = 35) using age-matched current or former (n = 11) and never smokers (n = 10) as controls. The data were analyzed in conjunction with the complete blood counts of the probands as well as the data about response to treatment and overall survival in the clinical trial. Results and conclusion: Untreated stage IV LCNEC patients had significant T-cell repertoire alterations (p < 0.001) compared to age-matched smokers. These changes correlated positively with blood lymphocyte counts (r = 0.49, p < 0.01), suggesting antigen-induced T-cell proliferation as the causative mechanism. At the same time, LCNEC patients showed mild lymphopenia (1.54 vs. 2.51/nl in median, p < 0.01), which reveals a second, antigen-independent mechanism of systemic immune dysregulation. More pronounced T-cell repertoire alterations and higher blood lymphocyte counts at diagnosis were associated with a better treatment response by RECIST and with a longer overall survival (441 vs. 157 days in median, p = 0.019). A higher degree of T-cell repertoire normalization after 3 months of therapy also distinguished a patient group with more favourable prognosis (median overall survival 617 vs. 316 days, p = 0.036) independent of radiological response. Thus, LCNEC induces clinically relevant changes of the T-cell repertoire, which are measurable in the blood and could be exploited for prognostic, predictive and therapeutic purposes. Their pathogenesis appears to involve antigen-induced oligoclonal T-cell expansions superimposed on TCR-independent lymphopenia.